2019
DOI: 10.1016/j.envpol.2019.01.118
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics analysis of a mouse model for chronic exposure to ambient PM2.5

Abstract: Chronic ambient fine particulate matter (PM 2.5) exposure correlates with various adverse health outcomes. Its impact on the circulating metabolome-a comprehensive functional readout of the interaction between an organism's genome and environment-has not however been fully

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 43 publications
4
30
0
Order By: Relevance
“…In the present study, the arti cial climatic environment exposure system (Shanghai-METAS) was used to study the effects of PM 2.5 exposure on kidney damage. This equipment which could maximally simulate "real world" PM 2.5 exposure is the rst comprehensive animal exposure system established in China, and has been effectively used to assess the effects of PM 2.5 exposure on health and diseases development in rodent in several studies (Du et al, 2018;Wang et al, 2018;Xu et al, 2019). Interestingly, the results of this study also con rmed that subchronic exposure to PM 2.5 led to kidney damage in SD rats.…”
Section: Discussionsupporting
confidence: 61%
“…In the present study, the arti cial climatic environment exposure system (Shanghai-METAS) was used to study the effects of PM 2.5 exposure on kidney damage. This equipment which could maximally simulate "real world" PM 2.5 exposure is the rst comprehensive animal exposure system established in China, and has been effectively used to assess the effects of PM 2.5 exposure on health and diseases development in rodent in several studies (Du et al, 2018;Wang et al, 2018;Xu et al, 2019). Interestingly, the results of this study also con rmed that subchronic exposure to PM 2.5 led to kidney damage in SD rats.…”
Section: Discussionsupporting
confidence: 61%
“…Collectively, these data provide a systemic and mechanistic rationale for coordination of the pineal and extrapineal synthesis of melatonin by a common damage‐associated stimulus in a megalopolis. It is well known that air pollution induces lung and systemic inflammatory responses . We confirm that acute exposure to particulate matter (2‐6 hours) induces an increase in circulating proinflammatory cytokines and show a transient increase in the transcription of proinflammatory genes and production of proinflammatory proteins, including TNF, in the pineal gland for the first time.…”
Section: Discussionsupporting
confidence: 79%
“…When animals that were exposed to polluted versus filtered air were compared, a significant reduction in plasma melatonin was detected after 4 hours in a polluted environment. Other authors that maintained animals under a polluted atmosphere for ten months confirmed a reduction in circulating melatonin after this long‐term exposure . Thus, as expected for an acute inflammatory response, a reduction in pineal melatonin synthesis was observed already during the first night.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…exposed to filtered air, and the altered metabolites were found to impact amino acid and lipid metabolism pathways. 123 Li et al also reported that human participants exposed to PM 2.5 showed a change in serum metabolites involved in glucose, amino acid, and lipid metabolism. 124 A recent study suggested that house dust may impair sphingolipid metabolism contributing to the development of an asthma phenotype.…”
mentioning
confidence: 96%